1980
DOI: 10.1029/gl007i012p01089
|View full text |Cite
|
Sign up to set email alerts
|

Thermally induced acoustic emission in westerly granite

Abstract: The acoustic emission of Westerly granite subjected to temperature changes up to 120° at various heating rates from 0.4 to 12.5°C/min was studied. A threshold temperature of 60 to 70°C appeared to exist for this range of heating rate, above which A.E. began to occur profusely with increasing temperature. Above the threshold temperature, the rate of A.E. depended strongly on the rate of heating. However, a thermal ‘Kaiser’ effect appeared to exist such that in cyclic heating and at temperatures below the maximu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
1
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(72 citation statements)
references
References 7 publications
5
65
1
1
Order By: Relevance
“…KE memory loss in rock, besides increasing time delay between successive loading cycles, can also be supported by water saturation and heating of rock which was shown by Yoshikawa and Mogi (1981). A thermal Kaiser , the recall of previous maximum temperature exists (Yong and Wang 1980;Zogala et al 1992;Shkuratnik et al 2007), while an aqua-Kaiser (recall of previous maximum humidity conditions) needs to be proven. No significant influence of loading rate on KE has been found (Lavrov 2001).…”
Section: Kaiser Effectmentioning
confidence: 91%
“…KE memory loss in rock, besides increasing time delay between successive loading cycles, can also be supported by water saturation and heating of rock which was shown by Yoshikawa and Mogi (1981). A thermal Kaiser , the recall of previous maximum temperature exists (Yong and Wang 1980;Zogala et al 1992;Shkuratnik et al 2007), while an aqua-Kaiser (recall of previous maximum humidity conditions) needs to be proven. No significant influence of loading rate on KE has been found (Lavrov 2001).…”
Section: Kaiser Effectmentioning
confidence: 91%
“…As more recent studies (e.g. Yong and Wang, 1980) have shown, microcracking of granite can occur with temperatures of 72°C or greater, so the combination of this with the effects of wetting and drying (caused by immersion in water followed by heating) could be expected to exacerbate the rate of breakdown.…”
Section: Details Of Mass Lossmentioning
confidence: 96%
“…Changes in dynamic (Alm et al, 1985;Petrakova et al, 2012) and static (Heard and Page, 1982;Homand-Etienne and Houpert, 1989;Heap et al, 2009;Petrakova et al, 2012) elastic moduli in response to thermal stressing showed that, whereas granites showed a deterioration in elastic moduli (e.g., Young's modulus was decreased by between 50-70%), extrusive igneous rocks (basalt and andesite) were unaffected. In the case of the extrusive igneous rocks, the unaltered elastic moduli were interpreted to be a consequence of their pre-existing pervasive thermal microcrack network (perhaps linked to the notion of the Kaiser "temperature memory" effect, see Yong and Wang, 1980;Zuberek et al, 1999;Choi et al, 2005) and their thermally stable mineral assemblages (Heap et al, 2009;Petrakova et al, 2012).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%